Linking Perceived Educational Support to Entrepreneur Intention: The Mediating Effect of Self-Confidence - Jadmiko, Purbo; Azliyanti, Elfitra; Putri, Tyara Dwi (Management Institute Faculty of Economics Universitas Andalas, 2019)
Applying the conceptual framework of value-attitude-behavior relationship, this study investigates self-confidence as mediating effect on the relationship between perceived educational support on entrepreneur intention. Using linier regression analysis, we investigate the role of self- confidence, perceived educational support on entrepreneur intention. In this paper, we used 160 students of economic faculty at Bung Hatta University. These results suggest that perceived educational support and self-confidence have positive effects on entrepreneur intention, and perceived educational support has positive effect on entrepreneur intention. This result shows self-confidence play an important role as a mediating variable on the relationship between perceived educational support on entrepreneur intention.